Efektivitas Pemberian Aromaterapi Lemon Dengan Aromaterapi Peppermint Dalam Mengurangi Emesis Gravidarum - Shinta Marlina; Riska Regia Catur Putri; Affi Zakiyya (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: During pregnancy, mother experienced some discomfort. One of them thatoccurred in early pregnancy was the appearance of nausea symptoms and vomiting (emesisgravidarum). If they were not treated immediately, it can cause hyperemesis gravidarum. Themanagement of nausea and vomiting can be done with complementary therapy, namely byusing aromatherapy. In this study, two types of aroma therapy were used, they were lemon andpeppermint aromatherapy. Objective: To determine the difference in the effectiveness of givinglemon and peppermint aromatherapy in reducing emesis gravidarum in first trimester ofpregnant women. Methods: This study used a quasi-experimental method with a two-grouppre-test and post-test design with a sample of 20 respondents using a simple random samplingtechnique. Data collection was carried out on May 20 to June 16, 2021 at Titin Widyaningsih’sMSP using the RINVR questionnaire. Results: There was a difference before and after beinggiven lemon aromatherapy in reducing nausea and vomiting in first trimester of pregnant womenwith the paired t-test, the p-value was 0.001. There was a difference before and after beinggiven peppermint aromatherapy in reducing nausea and vomiting in first trimester of pregnantwomen with the paired t-test, the p-value was 0.006. There was no difference between givingboth aromatherapy in reducing nausea and vomiting in first trimester pregnant women withindependent t-test p-value 0.738. Conclusion: There was an effect of lemon and peppermintaromatherapy in reducing emesis gravidarum in first trimester of pregnant women. There wasno difference between giving both aromatherapy in reducing nausea and vomiting in firsttrimester of pregnant women.Keywords: Emesis Gravidarum, RINVR, lemon and peppermint aromatherapy